Nordic Nutrition Recommendations 2012 Integrating nutrition and physical activity - Nordic Council of Ministers (Nordic Council of Ministers, 2014)
The Nordic countries have collaborated in setting guidelines for dietary composition and recommended intakes of nutrients for several decades through the joint publication of the Nordic Nutrition Recommendations (NNR). This 5th edition, the NNR 2012, gives Dietary Reference Values (DRVs) for nutrients, and compared with earlier editions more emphasis has been put on evaluating the scientific evidence for the role of food and food patterns contributing to the prevention of the major diet-related chronic diseases. Recommendations on physical activity are included and interaction with physical activity has been taken into account for the individual nutrient recommendations wherever appropriate. A chapter on sustainable food consumption has been added. A Nordic perspective has been accounted for in setting the reference values.The NNR 2012 has used an evidence-based and transparent approach in assessing associations between nutrients and foods and certain health outcomes. Systematic reviews form the basis for the recommendations of several nutrients and topics, while a less stringent update has been done for others. The systematic reviews and individual chapters have been peer reviewed and the systematic reviews are published in the Food & Nutrition Research journal. The draft chapters were subject to an open public consultation. Recommendations have been changed only when sufficient scientific evidence has evolved since the 4th edition. The primary aim of the NNR 2012 is to present the scientific background of the recommendations and their application. A secondary aim is for the NNR 2012 to function as a basis for the national recommendations that are adopted by the individual Nordic countries.